Effect of frying oils on the postprandial endoplasmic reticulum stress in obese people. Issue 11 (22nd September 2014) - Rangel‐Zuñiga, Oriol A.; Haro, Carmen; Perez‐Martinez, Pablo; Delgado‐Lista, Javier; Marin, Carmen; Quintana‐Navarro, Gracia M.; Tinahones, Francisco J.; Malagón, María M.; Lopez‐Segura, Fernando; López‐Miranda, Jose; Perez‐Jimenez, Francisco; Camargo, Antonio
<x xml:space="preserve">Abstract</x> The addition of antioxidants to frying oil reduces postprandial oxidative stress and the inflammatory response. ER stress may trigger both inflammation and oxidative stress processes. We aimed to determine the biological effects of the intake of four models of frying oils on postprandial ER stress in peripheral blood mononuclear cells. Twenty obese people received four breakfasts following a randomized crossover design, consisting of muffins made with different oils (virgin olive oil (VOO), sunflower oil (SFO), and a mixture of seed oils (SFO/canola oil) with either dimethylpolysiloxane (SOD) or natural antioxidants from olives (SOP) added), which were previously subjected to 20 heating cycles. ER stress was assessed by measuring the mRNA levels of sXBP1, BiP, CRT, and CNX in peripheral blood mononuclear cells. Our study showed that the intake of the muffins made with SFO induced the postprandial increase of the mRNA levels of the ER stress‐sensor sXBP1, and the ER stress related chaperones BiP and CRT (all p‐values <0.05). The harmful effects associated with the use of SFO as frying oil, in terms of inflammatory response and postprandial oxidative stress, may be partially mediated by the induction of postprandial ER stress.